Efektivitas Pelatihan Btcls Berbasis Blended Learning Terhadap Kepuasan dan Peningkatan Kompetensi Peserta di Bapelkes Mataram - Saimi Saimi; Hery Pranoto (Jurnal Ners, 2025)
Abstract Basic Trauma Cardiac Life Support (BTCLS) training has played an important role in improving the preparedness of health workers in dealing with emergency conditions. The blended learning method as a solution to limited resources and time, as well as to increase the effectiveness of training. Purpose: To find out the level of satisfaction and competency improvement of participants with BTCLS training based on blended learning. Methods: This study was a quantitative study using a cross-sectional survey of one group pre-post test design, with a sample of 73 trainees. Data were collected through standardized questionnaires and statistically analyzed using fisher exact test and paired t-test, with a significance level of p ≤ 0.005. Results: Showed that instructor quality, material accuracy, and organizer facilities were significantly related to participant satisfaction (Sig ≤ 0.01). The paired t-test also showed a significant increase in pre-test and post-test scores in all professional groups (p ≤ 0.05), so that the training provided proved to be effective in improving the competence of participants and needed to be continuously developed. Conclusion: The blended learning method has been shown to be effective in increasing trainee satisfaction and competence. The quality of the instructor and the relevance of the material are the main factors that affect participant satisfaction. Strengthening of practice aspects and curriculum adjustments is recommended to ensure the sustainability of BTCLS training. This research will be carried out at the Mataram Health Agency in 2025. Keywords: Participant satisfaction; BTCLS; Blended Learning; Quality of Instructors; Quality of Organizers